SPATIAL AND TEMPORAL ANALYSIS OF COVID-19 CASES IN PARAÍBA (International Seven Journal of Multidisciplinary, 2025)
This article focuses on performing a spatial and temporal analysis of COVID-19 cases in Paraíba. Spatial analysis of area data is used in geoprocessing when the occurrence of the phenomenon under study is measured based on aggregated data by area, such as the number of COVID-19 cases per city. A time series is a set of ordered observations (in time). Time can be spatial, deep, or other variables. R software was used for the analyses. The data were obtained from the Paraíba State Department of Health. The results of the spatial analysis showed that the number of cities with more than 1,000 COVID-19 cases increased in 2021, and a slight decrease in the number of COVID-19 cases in Paraíba in 2022. The cities of João Pessoa, Campina Grande, and Patos had the highest number of cases each year. In the temporal analysis, the data needed to be transformed to a Normal distribution to apply the Box-Jenkins technique. The most suitable model was the ARMA(2,1) model, which obtained the lowest values ​​for the selection criteria, the residuals also satisfied the conditions and the predicted values ​​were within the confidence interval.